Multi‐Level Anti‐Counterfeiting and Optical Information Storage Based on Luminescence of Mn‐Doped Perovskite Quantum Dots. Issue 18 (3rd July 2022) - Feng, Xuying; Sheng, Yuhang; Ma, Kewei; Xing, Fangjian; Liu, Cihui; Yang, Xifeng; Qian, Hongqiang; Zhang, Shude; Di, Yunsong; Liu, Yushen; Gan, Zhixing
Abstract: Traditional fluorescent anti‐counterfeiting labels can be easily cloned due to the lack of sufficient security. Therefore, multilevel anti‐counterfeiting techniques with higher security need to be constantly explored. This study reports a multilayer composite structure containing Mn doped CsPbCl3 (Mn:CsPbCl3 ) perovskite quantum dots (PQDs) layer and CsPbBr3 PQDs layer. The encrypted information is patterned on the Mn:CsPbCl3 PQDs layer with weak orange fluorescence, which is concealed by the brighter green fluorescence of CsPbBr3 PQDs at the upper layer. Based on the well‐separated photoluminescence (PL) peak positions, inverse PL temperature‐dependences and distinct PL lifetimes of these two PQDs, the encrypted information can be read out by adding cut‐off filter, heating and using ultrafast camera (UCA)/pulsed excitation (PE). This multilevel anti‐counterfeiting label significantly increases the difficulties of imitation meanwhile no expensive equipment is required for the verification of authenticity. Moreover, two bits of binary numbers that can be represented by dual emissions of the Mn:CsPbCl3 PQDs by changing the doping content, which significantly increases the information storage capacity, are also demonstrated. Abstract : A multilevel anti‐counterfeiting label is designed based on multilayer of perovskite quantum dots. The encrypted information can be read out by adding cut‐off filter, heating and using ultrafast camera/pulsed excitation. Moreover, two bits of binary numbers can be represented by dual emissions of the Mn:CsPbCl3 perovskite quantum dots, significantly increasing the information storage capacity.